Methanol induces low temperature resilient methanogens and improves methane generation from domestic wastewater at low to moderate temperatures. (August 2015) - Saha, Shaswati; Badhe, Neha; De Vrieze, Jo; Biswas, Rima; Nandy, Tapas
Graphical abstract: Highlights: Methanol improved methanogenesis of sewage, especially at <20 °C. Methanol, hydrogenotrophic methanogens and low temperature are connected. Methanol induced Methanobacteriales directly and Methanosetaceae indirectly. Both Methanobacteriales and Methanosetaceae grow abundantly at low temperature. Methanosetaceae are associated with homoacetogenic bacteria at low temperature. Abstract: Low temperature (<20 °C) limits bio-methanation of sewage. Literature shows that hydrogenotrophic methanogens can adapt themselves to low temperature and methanol is a preferred substrate by methanogens in cold habitats. The study hypothesizes that methanol can induce the growth of low-temperature resilient, methanol utilizing, hydrogenotrophs in UASB reactor. The hypothesis was tested in field conditions to evaluate the impact of seasonal temperature variations on methane yield in the presence and absence of methanol. Results show that 0.04% (v/v) methanol increased methane up to 15 times and its effect was more pronounced at lower temperatures. The qPCR analysis showed the presence of Methanobacteriales along with Methanosetaceae in large numbers. This indicates methanol induced the growth of both the hydrogenotrophic and acetoclastic groups through direct and indirect routes, respectively. This study thus demonstrated that methanol can impart resistance in methanogenic biomass to low temperature and can improve performance of UASB reactor.